(untitled) (قضايا سياسية, 2024)
Peace building is a process that involves investigating the deep causes of conflict by rebuilding the infrastructure as a whole. Peace building does not only address the remnants of Wars and Conflicts , but also addresses the causes that led to the outbreak of conflict. The Study of Peace building concludes that Peace building attempts include encouraging and developing Structural Conditions, attitudes, and patterns of political behavior that may allow for stable, peaceful, and ultimately prosperous Social and Economic prosperity. It is worth mentioning that there are four main headings related to peace building: providing Security, establishing the Social and Economic foundations for long-term peace, establishing the political framework for long-term peace, and generating reconciliation, which means healing the wounds of war and establishing justice.Accordingly, the Research attempts to define the boundaries of competencies Between the laws of war & peace building in light of Human Security through Three Axes in addition to the introduction and Conclusion.